Identification of WOX Family Genes in Selaginella kraussiana for Studies on Stem Cells and Regeneration in Lycophytes - Ge, Yachao; Liu, Jie; Zeng, Minhuan; He, Jianfeng; Qin, Peng; Huang, Hai; Xu, Lin (Frontiers in Plant Science, 2016)
Plant stem cells give rise to all tissues and organs and also serve as the source for plant regeneration. The organization of plant stem cells has undergone a progressive change from simple to complex during the evolution of vascular plants. Most studies on plant stem cells have focused on model angiosperms, the most recently diverged branch of vascular plants. However, our knowledge of stem cell function in other vascular plants is limited. Lycophytes and euphyllophytes (ferns, gymnosperms, and angiosperms) are two existing branches of vascular plants that separated more than 400 million years ago. Lycophytes retain many of the features of early vascular plants. Based on genome and transcriptome data, we identified WUSCHEL-RELATED HOMEOBOX (WOX) genes in Selaginella kraussiana, a model lycophyte that is convenient for in vitro culture and observations of organ formation and regeneration. WOX genes are key players controlling stem cells in plants. Our results showed that the S. kraussiana genome encodes at least eight members of the WOX family, which represent an early stage of WOX family evolution. Identification of WOX genes in S. kraussiana could be a useful tool for molecular studies on the function of stem cells in lycophytes.